(untitled) (Pedagogical Horizons, 2021)
Headteachers are facing more and more complex situations and challenges. Evidence make it obvious that headteacher feel quite stressed. The article reports outcomes based on case studies by interviews which have been part of a current research project. It points out the different challenges, some specific quality paradigms of headteachers, their leading strategies and their strategies to prevent stress. It has become obvious that the entrance into the leading position followed by the adaption of the system to the personal needs are acknowledged as very stressful. Whereas cooperative work, personal input, exchange in headteacher peer-groups and care are important markers for a satisfying professional and personal life.